The Crisis of Adab in Generation Z’s Social Interactions: Challenges and Urgency - Asyah, Nur; Fadhillah Putri, Rini; Fitriani, Enny (PT Inovasi Pratama Internasional, 2026)
Generation Z has grown up in the digital era marked by the massive dominance of social media and communication technologies. This phenomenon has significantly transformed patterns of social interaction—including attitudes, manners, and interpersonal communication ethics—often characterized by a decline in adab (ethical conduct) and face-to-face social skills. This study aims to identify the characteristics of the adab crisis in Generation Z’s social interactions, and examine the urgency of addressing this issue within the contexts of education and character development. A literature review method was employed to synthesize findings from recent empirical studies. The results indicate that the dominance of digital interactions contributes to a decline in meaningful interpersonal communication skills, while the need for adab education and soft skills development has become increasingly urgent. Theoretically, this study enriches the discourse on adab as a dynamic and contextual social construct in the digital era. Adab can no longer be understood solely in a normative–traditional sense but must be positioned as an adaptive social competence responding to contemporary changes. Practically, the findings provide a strong foundation for developing educational and guidance interventions—particularly through humanistic approaches and group guidance—as effective strategies for revitalizing adab in Generation Z’s social interactions